Identification and characterization of the COPII vesicle‐forming GTPase Sar1 in Chlamydomonas - Kin Pan Chung; Daniel Frieboese; Florent Waltz; Benjamin D. Engel; Ralph Bock (Plant Direct)
Abstract Eukaryotic cells are highly compartmentalized, requiring elaborate transport mechanisms to facilitate the movement of proteins between membrane‐bound compartments. Most proteins synthesized in the endoplasmic reticulum (ER) are transported to the Golgi apparatus through COPII‐mediated vesicular trafficking. Sar1, a small GTPase that facilitates the formation of COPII vesicles, plays a critical role in the early steps of this protein secretory pathway. Sar1 was characterized in yeast, animals and plants, but no Sar1 homolog has been identified and functionally analyzed in algae. Here we identified a putative Sar1 homolog (CrSar1) in the model green alga Chlamydomonas reinhardtii through amino acid sequence similarity. We employed site‐directed mutagenesis to generate a dominant‐negative mutant of CrSar1 (CrSar1DN). Using protein secretion assays, we demonstrate the inhibitory effect of CrSar1DN on protein secretion. However, different from previously studied organisms, ectopic expression of CrSar1DN did not result in collapse of the ER‐Golgi interface in Chlamydomonas. Nonetheless, our data suggest a largely conserved role of CrSar1 in the ER‐to‐Golgi protein secretory pathway in green algae.